2015
DOI: 10.1186/s12889-015-2429-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and care-seeking for chronic diseases among Syrian refugees in Jordan

Abstract: BackgroundThere are currently more people displaced by conflict than at any time since World War II. The profile of displaced populations has evolved with displacement increasingly occurring in urban and middle-income settings. Consequently, an epidemiological shift away from communicable diseases that have historically characterized refugee populations has occurred. The high prevalence of non-communicable diseases (NCDs) poses a challenge to in terms of provision of appropriate secondary and tertiary services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
176
4
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(204 citation statements)
references
References 13 publications
14
176
4
10
Order By: Relevance
“…Health care providers and Syrian refugees highlighted the high burden of chronic disease in this population, which is consistent with the World Health Organization data from Syria (15) and studies regarding Syrian refugees (16)(17)(18)(19)(20). Participants also identified the high smoking prevalence among Syrian refugees as a major contributor to the increase in chronic conditions.…”
Section: Discussionsupporting
confidence: 71%
“…Health care providers and Syrian refugees highlighted the high burden of chronic disease in this population, which is consistent with the World Health Organization data from Syria (15) and studies regarding Syrian refugees (16)(17)(18)(19)(20). Participants also identified the high smoking prevalence among Syrian refugees as a major contributor to the increase in chronic conditions.…”
Section: Discussionsupporting
confidence: 71%
“…The low percentage of patients with chronic diseases is not in line with Doocy et al (2015), who found a 50.3% of chronic diseases. First, the clinical setting in the present study was primarily for emergency medicine for patients en route, while the study in Jordan included settled refugees.…”
Section: Discussionmentioning
confidence: 81%
“…It is also possible that among settled refugees in nearby Jordan, more elderly people lived, while the present sample included mainly young and more mobile people, thus, with low frequency of chronic diseases. Indeed, when observing both Doocy et al (2015) and Cetorelli et al (2017), older age was correlated with higher prevalence of NCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations